2022
DOI: 10.1155/2022/5984184
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Correlation Analysis of Acute Coronary Syndrome with Serum IL‐18, MMP‐9, hs‐CRP, and Plasma FIB

Abstract: Aim. This study attempted to investigate the diagnostic value of interleukin-18 (IL-18), matrix metalloproteinase-9 (MMP-9), high-sensitivity C-reactive protein (hs-CRP), and fibrinogen (FIB) in acute coronary syndrome (ACS) and their correlation with the degree of vascular lesions. Materials and Methods. Altogether 206 patients with coronary heart disease admitted to our hospital were selected as research objects, including 136 patients with ACS (group A), 70 patients with stable angina pectoris (SAP) (group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The broad biological role of the IL-18 cytokine on immune cells have revealed its potential role in inflammatory and autoimmune diseases. IL-18 have been shown to be a diagnostic marker and predictor of inflammatory conditions like myocardial ischemia ( 106 ), acute respiratory distress syndrome ( 107 , 108 ), chronic obstructive pulmonary disease ( 109 ), post infectious bronchiolitis obliterans ( 110 ) and sepsis-induced multi organ injury ( 111 ). IL-18 has also received increase attention in the pathophysiology of neuro-vascular diseases such as in intracerebral hemorrhage ( 112 ), Japanese encephalitis ( 113 ), ocular Behcet disease ( 114 ), abdominal aortic aneurysm ( 115 ), amyotrophic lateral sclerosis ( 116 ), glioma ( 117 ) and most interestingly in cognitive impairment ( 118 ) and agitation in severe mental disease ( 119 ).…”
Section: Pathophysiological Autoimmune Conditions Associated With Il-18mentioning
confidence: 99%
“…The broad biological role of the IL-18 cytokine on immune cells have revealed its potential role in inflammatory and autoimmune diseases. IL-18 have been shown to be a diagnostic marker and predictor of inflammatory conditions like myocardial ischemia ( 106 ), acute respiratory distress syndrome ( 107 , 108 ), chronic obstructive pulmonary disease ( 109 ), post infectious bronchiolitis obliterans ( 110 ) and sepsis-induced multi organ injury ( 111 ). IL-18 has also received increase attention in the pathophysiology of neuro-vascular diseases such as in intracerebral hemorrhage ( 112 ), Japanese encephalitis ( 113 ), ocular Behcet disease ( 114 ), abdominal aortic aneurysm ( 115 ), amyotrophic lateral sclerosis ( 116 ), glioma ( 117 ) and most interestingly in cognitive impairment ( 118 ) and agitation in severe mental disease ( 119 ).…”
Section: Pathophysiological Autoimmune Conditions Associated With Il-18mentioning
confidence: 99%
“…In contrast, the subjects of this study are diabetes patients admitted for ACS occurrence. Research reports have shown that Hs-CRP levels in ACS patients are signi cantly higher than those in stable angina patients and healthy individuals [29]. Hs-CRP peaks on the second day after the occurrence of ACS and is much higher than the reference value.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, CRP is a marker of early myocardial injury that can be elevated within hours of the onset of myocardial damage. High-sensitivity CRP (hs-CRP) predicts the risk of cardiac events in asymptomatic populations and can assess the outcome of patients with acute coronary syndromes[ 36 , 37 ]. Chronic hyperglycaemia can induce vascular endothelial cell injury and an inflammatory response leading to DPN, while the inflammatory cytokines tumor necrosis factor-alpha and interleukin-6 can stimulate CRP synthesis in vivo [ 38 ].…”
Section: Cardiovascular Inflammatory Markersmentioning
confidence: 99%